Modeling the Exports Diversification in the Oil Countries Growth: The Case of Gulf Cooperation Council Countries - Alomari, Mohammad W.; Bashayreh, Ala' G. (International Journal of Energy Economics and Policy, 2020)
This paper aims at modeling and analyzing the short and long run effects of export diversification on economic growth using the countries Gulf Cooperation Council (GCC) panel data for the period 1992–2017. The paper introduces the panel Auto Regressive Distributed Lag/ Pooled Mean Group (ARDL/PMG) to reach its purpose. The export diversification measured by Theil index. The Pedroni panel cointegration test confirms that the variables are cointegrated, whereas Pooled Mean Group (PMG) estimates indicate a positive significant long run relationship between export diversification and real GDP growth, no significant effect of export diversification in the short run. Results reveal a significant impact of trade openness growth on real GDP growth, which confirms the long-run as well as the short-run relationship between the growth of trade openness and economic growth for the GCC countries. it is worth to mention that the overall effort for GCC region on average had succeed in diversification, and the achieving of their plans goal is start to appear as a long run effect. but the study reveals that results may differ relatively in each country. Keywords: Economic growth; Economic diversification; Oil Countries; Trade openness; Structural reform; Panel ARDL/ PMG. JEL Classifications: C10, C33, F11, F14, F43, O11, O13 DOI: https://doi.org/10.32479/ijeep.8977